Konsep Kekayaan dalam Pemikiran Ekonomi Islam: Perbandingan Ibnu Taimiyyah dan Yusuf Qardhawi - Setiawan, Nanda; Ghani, Wan Ruslan Abdul; Mahfudz, Agus (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2024)
The concept of wealth in Islam is profound and complex, influenced by the principles of Sharia found in the Qur'an and Hadith. Understanding of this concept evolves with the changing times, and influential scholars such as Ibn Taymiyyah and Yusuf al-Qaradawi have made significant contributions in this regard. This study aims to analyze a comparative view of the two scholars on property ownership and its implications for contemporary Islamic economic practices. The research method employed is a literature review, with data collection through reading and analyzing sources from the works of Ibn Taymiyyah and Yusuf al-Qaradawi. The collected data is analyzed using a comparative approach to identify the similarities and differences in the views of the two scholars. The findings of the study show that while both scholars agree that wealth is a trust from Allah, they emphasize different aspects of the purpose and mechanisms of wealth distribution. Ibn Taymiyyah emphasizes the individual's role in property ownership, while Yusuf al-Qaradawi focuses more on social justice and the role of the state in wealth distribution. The implications of these findings contribute significantly to the development of contemporary Islamic economics, particularly in the areas of business ethics, social justice, the role of the state, and innovations in finance based on Sharia principles.